Alcohol consumption and the sense of coherence in young people in educational training - Moutinho, Lidia Susana Mendes (2015)
The rate of consumption of alcoholic beverages has undergone changes as well as the factors that influence it. In order to understand the significance of drinking patterns, this study was conducted with a sample of young adults (N = 260) ages 20 to 30, in Lisbon. The instruments used were The Alcohol Use Disorders Identification Test and the Sense of Coherence Questionnaire. The results show that 10.8% had problems with alcohol. Those who had a lower sense of coherence, especially in the dimension of investment capacity, presented with more harmful and risky consumption patterns. We conclude that health promotion behaviors should include measures to strengthen a sense of coherence